Tahiti 8 Conference: From Material to Immaterial - Johanna Frigård; Roni Grén; Katve-Kaisa Kontturi; Tutta Palin; Riikka Stewen (Taidehistorian Seura, 2022)
Conference publication from Tahiti 8 Conference: From Material to Immaterial: Art Historical Practices in the Contemporary World (University of Turku, 28–29 November 2019).